-3(x-4)+4=-4(3x-3)+6+13x

Simple and best practice solution for -3(x-4)+4=-4(3x-3)+6+13x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x-4)+4=-4(3x-3)+6+13x equation:


Simplifying
-3(x + -4) + 4 = -4(3x + -3) + 6 + 13x

Reorder the terms:
-3(-4 + x) + 4 = -4(3x + -3) + 6 + 13x
(-4 * -3 + x * -3) + 4 = -4(3x + -3) + 6 + 13x
(12 + -3x) + 4 = -4(3x + -3) + 6 + 13x

Reorder the terms:
12 + 4 + -3x = -4(3x + -3) + 6 + 13x

Combine like terms: 12 + 4 = 16
16 + -3x = -4(3x + -3) + 6 + 13x

Reorder the terms:
16 + -3x = -4(-3 + 3x) + 6 + 13x
16 + -3x = (-3 * -4 + 3x * -4) + 6 + 13x
16 + -3x = (12 + -12x) + 6 + 13x

Reorder the terms:
16 + -3x = 12 + 6 + -12x + 13x

Combine like terms: 12 + 6 = 18
16 + -3x = 18 + -12x + 13x

Combine like terms: -12x + 13x = 1x
16 + -3x = 18 + 1x

Solving
16 + -3x = 18 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
16 + -3x + -1x = 18 + 1x + -1x

Combine like terms: -3x + -1x = -4x
16 + -4x = 18 + 1x + -1x

Combine like terms: 1x + -1x = 0
16 + -4x = 18 + 0
16 + -4x = 18

Add '-16' to each side of the equation.
16 + -16 + -4x = 18 + -16

Combine like terms: 16 + -16 = 0
0 + -4x = 18 + -16
-4x = 18 + -16

Combine like terms: 18 + -16 = 2
-4x = 2

Divide each side by '-4'.
x = -0.5

Simplifying
x = -0.5

See similar equations:

| 16m=76 | | 2x-5y=-25 | | 4(3x+8)=80 | | 6(5x+11)-9x= | | 35=-7+3n | | 23n-24n= | | 2=15x^2+x | | y=0.13x+585 | | 4(3n+3)=9(9n+1)+5 | | (x-(8/x))^2-5(x-(8/x))-14=0 | | 12x-127=4x+169 | | (8x^4-2x^2+3x-5)-(2x^4+x^3+3x+5)= | | (3x+3)+(15-3x)= | | 7(2n+2)=7(7n+7)+9 | | 4(q)+(-1)(1-q)=1(q)+2(1-q) | | -4n(6n-5)+3n= | | 5(x+3)=4x+14 | | 0.9x-5.3=0.1 | | (9x-6)+6= | | 2+-6m=-4m+10 | | -9(y-1)=2-8y | | -3x(x+5)-7=-8+10 | | 3a-(5-3a)=10 | | 4(q)+(-1)(1-q)=1q+2(1-q) | | 5x+-6=3x+-8 | | (3-x)+(x-4)=2(x+4) | | w=-125t+6000 | | -6+5(-9x-3)=-10 | | -6+(-9x-3)=-10 | | 24+r=28 | | 5p+8=-32 | | 2=-19+z |

Equations solver categories